Estudo e aplicação da função polinomial do 1º grau: uma metodologia de ensino com batedores de açaí no município de Barcarena - PA - MELO, Marcus Vinícius de Sousa (2022)
The present course conclusion work aims to present a methodology for teaching the Polynomial Function of the 1st Degree, which emerged from the hypothesis of showing that its content can be linked to the reality of the students, highlighting and directing to a learning in which the subject addressed will be understood by students in situations where use and application are guided by an effective and contextualized teaching and learning process. The application of the function will be carried out from the research with açaí scouts belonging to the municipality of Barcarena where the theory of function in the sale of açaí juice can be used in the activity. That is, in marketing, seeking to evaluate the applicability of the function's content in problem situations, emphasizing profits or financial balance with the sale of the product. Knowledge can be shared not only abstractly in the classroom, but introduced into the student's daily life. From the information obtained, two examples will be used at the student's level of knowledge, namely: the açaí juice trade and palm extractivism, in addition to dealing with the theoretical foundation from the definition, concept of angular and linear coefficients, construction of graphs, growth and decrease conditions and 1st degree inequalities. The research concludes considering that the teaching and learning process can be better understood in the context of the classroom when the teacher seeks a methodology that is linked to theory and practice.